The seductive allure of neuroscience explanations - Weisberg, Deena Skolnick; Keil, Frank C; Goodstein, Joshua; Rawson, Elizabeth; Gray, Jeremy R (Journal of cognitive neuroscience, 2008)
Explanations of psychological phenomena seem to generate more public interest when they contain neuroscientific information. Even irrelevant neuroscience information in an explanation of a psychological phenomenon may interfere with people's abilities to critically consider the underlying logic of this explanation. We tested this hypothesis by giving naïve adults, students in a neuroscience course, and neuroscience experts brief descriptions of psychological phenomena followed by one of four types of explanation, according to a 2 (good explanation vs. bad explanation) x 2 (without neuroscience vs. with neuroscience) design. Crucially, the neuroscience information was irrelevant to the logic of the explanation, as confirmed by the expert subjects. Subjects in all three groups judged good explanations as more satisfying than bad ones. But subjects in the two nonexpert groups additionally judged that explanations with logically irrelevant neuroscience information were more satisfying than explanations without. The neuroscience information had a particularly striking effect on nonexperts' judgments of bad explanations, masking otherwise salient problems in these explanations.
Keywords: Adolescent; Adult; Cognition; Female; Humans; Judgment; Male; Middle Aged; Personal Satisfaction; Probability Learning; Psychological Theory; neurosciences